Diurnal fluctuations of subthalamic nucleus local field potentials follow naturalistic sleep-wake behavior in Parkinson's disease - Baumgartner, Alexander J; Hirt, Lisa; Amara, Amy W; Kern, Drew S; Thompson, John A (Sleep (New York, N.Y.), 2025)
Deep brain stimulation (DBS) of the subthalamic nucleus (STN) may improve sleep dysfunction, a common non-motor symptom of Parkinson's disease (PD). Improvement in motor symptoms correlates with DBS-suppressed local field potential (LFP) activity, particularly in the beta frequency (13-30 Hz). Although well-characterized in the short term, little is known about the innate progression of these oscillations across the sleep-wake cycle. We sought to characterize LFP fluctuations over several days and nights in the home setting in patients chronically treated with DBS. LFPs in the beta and alpha frequency range were recorded from the STN in 13 PD subjects (18 hemispheres) over 14.6 (interquartile range 4) days. Sleep and wake were determined by validated actigraphy. We calculated the mean difference between sleep and wakefulness in LFP power (µVp), probability density functions of normalized LFP, and the fraction of overlap between probability density histograms. STN LFPs showed a consistent fluctuation based on behavioral state. LFP power was higher during wakefulness than during sleep, with little overlap in the magnitude of LFP power between these two states. Delineation of subject activity patterns revealed that LFP variance by time of day was more strongly correlated at night. STN LFP fluctuations represent a useful measure to distinguish between sleep and wakefulness in PD. These fluctuations can be detected in the home setting using commercially available devices, including in patients who have been treated with DBS for years. This technology may lead to opportunities for closed-loop DBS therapy.